ChemInform Abstract: Synthesis of 3, 3‐Disubstituted Indoline‐2‐thiones Catalyzed by an N‐Heterocyclic Carbene. Issue 1 (January 2015) - Ikota, Hideo; Ishida, Takayuki; Tsukano, Chihiro; Takemoto, Yoshiji
Abstract Successive treatment of α, β‐unsaturated aldehydes such as (I) and (IV) bearing an isocyanato moiety with an in situ generated NHC‐catalyst and an appropriate heteroatomic nucleophile provides title compounds (III), (VI), and (VIII) in moderate to good yields.